Identification and Law Review of Closed Agreements in Indonesia: Analysis of Case Closed Agreements PT. Pelindo II Persero in Teluk Bayur Port, Padang, West Sumatra Province - Dani Amran Hakim (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
This paper aims to identify and analyze on a law review of closed agreements by the Law Number 5 of 1999 on Prohibition of Monopolistic Practices and Unfair Competition as well as how the legal analysis of the alleged cases of agreements covered by PT Pelindo II (Persero) which occurred in Teluk Bayur in Padang, West Sumatra. In a legal review of the closed agreement as mentioned in Article 15 and 19 of Law Unfair Competition, it can be concluded that the closed agreements carried out in a business relationship tend to be favorable to the parties entered into a secretive and harmful for others who are not inside the circle of the agreement. Case Lease Agreement of Land between PT Pelindo II (Persero) with a third party is tying product whereas clauses designation stevedoring companies owned by PT Pelindo II (Persero) for the tenants are tied product, and the agreement is contrary to the principle of fair business competition especially Article 15 paragraph (2) of Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. Keyword: Identification, Closed Agreements, PT Pelindo II